Delivering business analytics practical guidelines for best practice - Stubbs, Evan (Gildan Audio, 2020)
Unlocking the value of business analytics can be challenging complexity, uncertainty, and confusion are usually the norm, not the exception. True innovation and competitive advantage stem from navigating the razors edge between order and chaos. So how do those who succeed do it' Everyone faces the same challenges; success comes from balancing the benefits of unfettered creativity with the need to industrialize those same unstructured processes. The harsh reality is that most teams are not as effective at managing these competing pressures as they could be. With the information contained in this book, they would be. This book provides 30 design patterns (examples) to help guide those who would create value through business analytics. Practical advice is given to help understand: (a) how a variety of common problems can be solved; (b) the advantages of disadvantages of each choice; and (c) how these solutions typically create organizational value. Each Pattern will contain the following elements: (a) pattern diagram, (b) problem the pattern solves, (c) design intent behind the pattern, (d) description of the actors and entities involved in the pattern, (e) use case description, (f) benefits of the approach, (g) limitations of the approach, and (g) common business-related applications and the reason why the pattern creates value.